BodyWise: Evaluating a Pilot Body Image Group for Patients with Anorexia Nervosa. (9th November 2014) - Mountford, Victoria A.; Brown, Amy; Bamford, Bryony; Saeidi, Saeideh; Morgan, John F.; Lacey, Hubert
Abstract Body image disturbance can be enduring and distressing to individuals with eating disorders and effective treatments remain limited. This pilot study evaluated a group‐based treatment—BodyWise—developed for use in full and partial hospitalization with patients with anorexia nervosa at low weight. A partial crossover waitlist design was used. BodyWise (N = 50) versus treatment as usual (N = 40) were compared on standardized measures of body image disturbance. Results demonstrated significant improvement in the group compared to treatment as usual for the primary outcome measure (Eating Disorder Examination—Questionnaire Shape Concern subscale) and other manifestations of body image disturbance including body checking and body image quality of life. BodyWise appeared acceptable to participants, and was easy to deliver within the pragmatics of a busy eating disorder service. There is potential for its wider dissemination as a precursor to more active body image interventions. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.